2008
DOI: 10.1093/ecam/nen027
|View full text |Cite
|
Sign up to set email alerts
|

Yoga Practice for the Management of Type II Diabetes Mellitus in Adults: A systematic Review

Abstract: The effect of practicing yoga for the management of type II Diabetes was assessed in this systematic review through searching related electronic databases and the grey literature to the end of May 2007 using Ovid. All randomized controlled clinical trials (RCTs) comparing yoga practice with other type of intervention or with regular practice or both, were included regardless of language or type of publication. Each study was assessed for quality by two independent reviewers. Mean difference was used for summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 40 publications
(43 reference statements)
3
92
0
3
Order By: Relevance
“…the Hypothalamic Pituitary Adrenal (HPA) axis, AMP kinase pathway, reduction in oxidative stress and pro-inflammatory markers and enhanced parasympathetic activity. [13][14][15][16] No adverse effects were reported in any of the previous studies involving type 2 diabetes patients, ensuring yoga to be a safe and effective complementary therapy in the management and prevention of complications of diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…the Hypothalamic Pituitary Adrenal (HPA) axis, AMP kinase pathway, reduction in oxidative stress and pro-inflammatory markers and enhanced parasympathetic activity. [13][14][15][16] No adverse effects were reported in any of the previous studies involving type 2 diabetes patients, ensuring yoga to be a safe and effective complementary therapy in the management and prevention of complications of diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence for the benefits of yoga practice includes its effects shown to decrease the diabetes [5][6]. Many previous studies have shown physical exercise is beneficial and decreases diabetes [7][8] [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review found that tai chi had no significant effects on glycemic control or quality of life (32). Another systematic review evaluating yoga as an intervention for type 2 diabetes found modest reductions in glycated hemoglobin (A1C), fasting glucose and total cholesterol levels, as well as modest increases in high-density lipoprotein cholesterol (33). However, the quality of the included studies was low, and results were inconsistent.…”
Section: Peripheral Neuropathymentioning
confidence: 99%